Pengaruh Gaya Kepemimpinan, Komitmen Organisasi, Budaya Organisasi terhadap Kepuasan Kerja dan Kinerja Karyawan Pemasaran (pada Dealer Motor PT Suzuki Cabang Madiun dan Ngawi) - Robby Sandhi Dessyarti (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2018)
The aim of this research is to describe and examine the influence of leadership style, organizational commitment, organizational culture on job satisfaction and employee performance, the influence of job satisfaction on employee performance. While examining the influence of indirect leadership style, organizational commitment, organization culture on employee performance through job satisfaction in PT Suzuki, Madiun and Ngawi branches motor dealer. The population used is the entire marketing employees as much as 136 people, total sampling or the census technique conducted. The questionnaire with five dimensions likert scale data, with SPSS assistance and Structural Equation Modeling AMOS analyzing method. The validity and reliability of the data tested by covergent validity and construct reliability next to the Goodness of Fit evaluation criteria. The results of the data analysis concluded that leadership style, organizational commitment, organizational culture do have positive and significant impact on job satisfaction and employee performance, while job satisfaction do have positive and significant impact on the employees performance. Job satisfaction does not mediating between leadership styles, organizational commitment and organizational culture on employee performance in PT Suzuki, Madiun and Ngawi branches motor dealer.